Endangerment of Ruruuli-Lunyala language: Past and current trends - Namyalo, Saudah (Stellenbosch Papers in Linguistics Plus, 2023)
Ruruuli-Lunyala (JE.103; Glottocode: ruul1235, ISO 639-3: ruc) is the native language of the Baruuli and Banyala ethnic groups of Uganda. It is one of the most endangered and under-described languages in Uganda (see Namyalo et al. 2021; Nakayiza 2013). This paper analyses the factors that caused the endangerment of Ruruuli-Lunyala from a historical perspective. It further provides an overview of its current status and the steps that have been taken by the community towards its revitalisation. The data for this paper were collected using oral interviews, observations, and document analysis. The results of the study indicate that the main cause of Ruruuli-Lunyala endangerment stems from the Buganda colonial administration. Under the Buganda rule, Ruruuli-Lunyala language as well as the Kiruuli-Kinyala culture were abandoned. This and other factors explain why this language remains one of Uganda’s under-described minority languages. The study concludes by observing that, although there are some support efforts towards the revitalisation of Ruruuli-Lunyala, the young population is shifting to Luganda, Runyoro and Lusoga.